A high rate zinc/MCM-41/air cell - Saputra, Hens; Othman, Raihan (ISESCO Center for Promotion of Scientific Research (ICPSR), 2012)
We report the performance characteristics of a high discharge rate zinc-air cell, assembled in a compact, monopolar and bipolar configurations. The use of inorganic MCM-41 membrane enables the construction of a thin, compact cell design with ease. MCM-41 consists of hexagonally-ordered nanopore structure and characterized by its large surface area and pore volume, very narrow pore size distribution, hydrophilic in nature and very good thermal stability. The monopolar Zinc/MCM-41/air cell demonstrates discharge characteristics of comparable performance to commercial cells. The cell, 1 cm2 area x ca. 460 µm thick, possesses limiting current of 27 mA, maximum power output of 31 mW, and volumetric energy density of 924 Wh/l, rated at 20 mA. A bipolar design markedly improves the cell performance. The cell, 1 cm2 area x ca. 920 µm thick, possesses limiting current of 95 mA, maximum power output of 107 mW, and volumetric energy density of 1189 Wh/l.